SINERGI TIGA GAYA KEPEMIMPINAN KEPALA SEKOLAH: STUDI KASUS IMPLEMENTASI DEMOKRATIS, LAISSEZ-FAIRE, DAN TRANSFORMASIONAL DI SMAN - Herlina, Besse; Aminah, Sitti; Wahyuddin, Wahyuddin; Hairawati, Hairawati; Hasriani, Hasriani; Rahmawati, Rahmawati; Ratnawati, Ratnawati (Jurnal Administrasi Pendidikan Indonesia, 2025)
Challenges include limited facilities, human resource constraints, and the need to improve learning quality. This study aims to analyze the implementation of democratic, laissez-faire, and transformational leadership styles applied by SMAN principals in carrying out managerial and educational leadership functions. The study used a descriptive qualitative approach, with data collected through direct observation, in-depth interviews, and reviews of school documentation. The research subjects consisted of 1 principal, 15 teachers, 10 students, and five educational staff. The results showed that the democratic leadership style was applied in strategic decision-making and the formation of school policies involving various parties. Meanwhile, the laissez-faire approach was used in teacher professional development and the implementation of extracurricular activities, in which the principal granted full autonomy to teachers and students. On the other hand, the transformational leadership style was reflected in an inspirational vision, encouragement of learning and innovation, and the formation of an adaptive and collaborative school culture. The combination of these three leadership styles demonstrated effectiveness in creating a positive learning environment, empowering all school components, and encouraging improvements in the quality of education. The implications of this study provide an overview of the importance of flexibility and contextual sensitivity in principal leadership in developing areas.